Legal Protection of Gig Economy Workers: A Comparative Study in Indonesia, Malaysia, and Singapore - Lesmana, Sri Jaya; Samudra, Muhammad Mpu (SASI, 2025)
Introduction: With the rapid growth of the digital economy, gig workers, who are generally classified as independent contractors, often do not have adequate legal and social security protections compared to conventional workers.Purposes of the Research: This study presents a comparative analysis of legal protection for gig economy workers in three Southeast Asian countries, namely Indonesia, Malaysia, and Singapore. The study focuses on the regulatory framework applicable in each country, covering aspects of labor laws as well as various other regulations or policies related to workers' rights and social protection guarantees.Methods of the Research: Normative legal research methods are used to examine policies related to workers in the performing economy sector in Indonesia, Malaysia, and Singapore. This approach is used to compare the legal protection provided to these workers in the three countries, by referring to the provisions of the applicable laws and regulations in each country.Results of the Research: The results show that despite differences in regulatory approaches, the three countries still face significant challenges in creating adequate social safety nets. The researcher recommends that harmonization and innovation in labor policies need to be carried out to achieve a balance between work flexibility and the protection of workers' rights. In addition, the development of more inclusive and sustainable regulations in the digital era should also be carried out.